Equilibrium And Kinetics Of Disperse Dye Adsorption On Activated Carbon Prepared From Rattan Sawdust By Chemical Activation. - Ahmad, A.A.; Hameed, B.H.; Ahmad, A.L. (2008)
The liquid-phase adsorption of C.I. Disperse Orange 30 (DO30) onto activated carbon prepared from rattan sawdust by chemical activation with H3PO4. The rattan sawdust was carbonized at 500oC, 2h and impregnated ratio weight with H3PO4 at 1:4.5.